Application of Laplace Differential Transform Method in Solving Two-Dimensional Partial Differential Equations with Variable Coefficient - Daniel, Deborah Oluwatobi (Naresuan University Journal: Science and Technology (NUJST), 2021)
In this paper, Laplace Differential Transform Method (LDTM) is employed in solving two-dimensional partial differential equations with variable coefficients. Laplace Differential Transform Method (LDTM) combines Laplace transform and Differential Transform Method (DTM) and can be used to effectively solve 2-D partial differential equations. In order to demonstrate the effectiveness of this method, 2-D heat-like equations and wave-like equation were considered. Results revealed that the LDTM is effective and efficient in handling 2-D homogeneous and nonhomogeneous partial differential equations with little computational effort. Keywords:   Nonhomogeneous PDE, 2-D PDE, Laplace Differential Transform Method, Laplace Transform, Differential Transform Method